Biolinguistics - Boeckx, Cedric A.; Martins, Pedro Tiago; Leivada, Evelina (My University, 2017)
IntroductionComing across a contribution that deals with the biological foundations of the human language faculty in a handbook that is dedicated to historical syntax is likely to surprise many. Is the human language faculty not uniform? And is historical change not a cultural process, rather than a biological one? We would like to use this introduction to make a few things clear. First, although our chapter is located next to those dealing with theoretical frameworks like Principles and Parameters, we insist on biolinguistics being taken not as an alternative framework (synonymous with, say, Minimalism), but as an orientation for linguistic studies, within which choice of framework is appropriate. Second, we follow the generative tradition that takes language change to be closely tied to language acquisition and typology. And in this context biolinguistic considerations lead us to an important and surprising conclusion: natural language syntax is invariant. It is not subject to variation, and therefore not subject to change. At least within our species. We could, of course, talk about syntactic change in a biolinguistic context by focusing on differences between natural language syntax and birdsong syntax. There, of course, there has been a significant syntactic change. But we feel that this topic is not what readers of this handbook might expect, and so we will leave it aside (interested readers can turn to Boeckx 2012; Berwick et al. 2012). Third, there is a sense in which the much discussed ‘Darwin problem’ in the recent biolinguistic literature really pertains to language change. As is well known, Darwin did not really discuss the origin of species in his most famous book, if by that we mean ‘emergence of form’: he focused on historical changes once the relevant form had emerged. As such, we agree with Koji Fujita (p.c.) that Darwin would have been more interested in the emergence of specific grammatical systems (language change) rather than in the emergence of a species with a language-ready brain (the latter problem may have interested Turing far more, so we could call it Turing's problem). That said, we do not want to suggest that biolinguistics has nothing to contribute to studies of language change. Quite apart from establishing that syntactic change is non-existent, biolinguistic considerations help refine our understanding of notions like I(nternal)-language and E(xternal)-language (Chomsky 1986) that have figured prominently in the literature on (alleged) syntactic change.
Keywords: Language; Historical syntax; Biolinguistic; Darwin problem